2020
DOI: 10.3390/su12010351
|View full text |Cite
|
Sign up to set email alerts
|

Application of Life Cycle Energy Assessment in Residential Buildings: A Critical Review of Recent Trends

Abstract: Residential buildings are responsible for a considerable portion of energy consumption and greenhouse gas emissions worldwide. Correspondingly, many attempts have been made across the world to minimize energy consumption in this sector via regulations and building codes. The focus of these regulations has mainly been on reducing operational energy use, whereas the impacts of buildings’ embodied energy are frequently excluded. In recent years, there has been a growing interest in analyzing the energy performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 58 publications
0
38
0
1
Order By: Relevance
“…LCEA is a version of the LCA that only accounts for energy usage at all stages of a building's life cycle [6,24]. In this approach, the total energy performance of a building is quantitatively assessed considering both operational and embodied energies.…”
Section: An Overview Of Lceamentioning
confidence: 99%
See 2 more Smart Citations
“…LCEA is a version of the LCA that only accounts for energy usage at all stages of a building's life cycle [6,24]. In this approach, the total energy performance of a building is quantitatively assessed considering both operational and embodied energies.…”
Section: An Overview Of Lceamentioning
confidence: 99%
“…Currently, the literature is lacking such a comprehensive framework. This lack is reflected in the findings of recent studies that reported variations in the results of life cycle energy assessment (LCEA) analyses [22][23][24][25][26]. In a recent study, Pan and Teng [26] conducted a holistic literature review analysis of 244 case studies, aiming to quantify potential variations in embodied energy calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It allows us to select the most ap-propriate systems that will provide an efficient and sustainable design reducing this way the building's Heating Ventilation and Air Conditioning (HVAC) loads. By designing a sustainable building method, the use of energy, water, land, and raw materials must be minimized, reducing emissions, pollution, waste and also the running costs of any building [7]. A sustainable construction should be energy efficient and cheaper to run, durable, and made of environmentally friendly materials so waste during the whole construction period should be considered, for both cost and environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…Across the world, the energy requirement is increasing rapidly due to the attraction of urbanization facilities and the human population [6][7][8]. The world's largest CO 2 contributors are buildings, as the current building structures are demolished and rebuilt as huge buildings like skyscrapers to accommodate the population in urban areas [9][10][11].…”
Section: Introductionmentioning
confidence: 99%